2021
DOI: 10.1111/jpi.12716
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects inner retinal neurons of newborn mice after hypoxia‐ischemia

Abstract: Retinopathy of prematurity is a vision-threatening disease associated with retinal hypoxia-ischemia, leading to the death of retinal neurons and chronic neuronal degeneration. During this study, we used the oxygen-induced retinopathy mice model to mimic retinal hypoxia-ischemia phenotypes to investigate further the neuroprotective effect of melatonin on neonatal retinal neurons. Melatonin helped maintain relatively normal inner retinal architecture and thickness and preserve inner retinal neuron populations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 65 publications
(186 reference statements)
2
34
0
Order By: Relevance
“…Matusica et al [ 21 ] indicated that BDNF enables P75 (NTR)-derived trophic cell permeapeptides (c29) to promote neuronal survival through the TrkB-dependent signaling pathway in vitro and in vivo. The BDNF/TrkB pathway in learning and memory [ 22 ], chronic pain [ 23 ], and retinopathy [ 24 ] has been deeply studied, but there are few studies on neuronal apoptosis. BDNF-AS is a natural antisense transcript that inhibits the transcription of BDNF [ 15 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Matusica et al [ 21 ] indicated that BDNF enables P75 (NTR)-derived trophic cell permeapeptides (c29) to promote neuronal survival through the TrkB-dependent signaling pathway in vitro and in vivo. The BDNF/TrkB pathway in learning and memory [ 22 ], chronic pain [ 23 ], and retinopathy [ 24 ] has been deeply studied, but there are few studies on neuronal apoptosis. BDNF-AS is a natural antisense transcript that inhibits the transcription of BDNF [ 15 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence of iridal frozen sections and flat mounts of anterior lens capsule was performed as described previously. 27 29 Briefly, the tissues were permeated for 20 minutes and blocked with 5% normal goat serum for two hours at 25°C. Then, the tissues were incubated with primary antibodies overnight at 4°C, followed by a corresponding secondary antibody for two hours ( Supplementary Table S3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescent staining of whole retinal mounts, frozen sections, and HUVEC was performed as described previously. 28 , 29 All fluorescence images were taken using confocal laser scanning microscopy (LSM880, Carl Zeiss, Jena, Germany). For whole retinal mounts, six retinas were analyzed per experimental group and the extent of neovascular or avascular area were expressed as the percentage of the number of pixels in the neovascular tuft area/ avascular area relative to the number of pixels in the total retinal area.…”
Section: Methodsmentioning
confidence: 99%
“…HE staining was applied as described previously. 28 Sections were imaged using a light microscope (Leica, Frankfurt, Germany) to measure the number of vitreoretinal neovascular cells nuclei. A quantitative approach to HE staining kept consistent with what was detailed elsewhere in this article for the quantitation of the frozen sections.…”
Section: Methodsmentioning
confidence: 99%